Gerontocracy of the Buddhist monastic administration in Thailand - Jesada Buaban (Universitas Trunojoyo Madura, 2021)
This paper examines the monastic administration in Thai Buddhism, which is ruled by the senior monks and supported by the government. It aims to answer two questions; (1) why the Sangha’s administration has been designed to serve the bureaucratic system that monks abandon social and political justices, and (2) how the monastic education curriculum are designed to support such a conservative system. Ethnographic methodology was conducted and collected data were analyzed through the concept of gerontocracy. It found that (1) Thai Buddhism gains supports from the government much more than other religions. Parallel with the state’s bureaucratic system, the hierarchical conservative council contains the elderly monks. Those committee members choose to respond to the government policy in order to maintain supports rather than to raise social issues; (2) gerontocracy is also facilitated by the idea of Theravada itself. In both theory and practice, the charismatic leader should be the old one, implying the condition of being less sexual feeling, hatred, and ignorance. Based on this criterion, the moral leader is more desirable than the intelligent. The concept of “merits from previous lives” is reinterpreted and reproduced to pave the way for the non-democratic system.